Credit counseling: A substitute for consumer financial literacy? - Richard Disney; John Gathergood; Jörg Weber (Institute for Fiscal Studies (IFS), 2014)
Is financial literacy a substitute or complement for financial advice? In this paper we analyze the decision by consumers to seek financial advice in the form of credit counseling concerning their credit and debt. Credit counseling is an important component of the consumer credit sector for consumers facing debt problems.We combine instrumental variable approaches to account for the endogeneity of an individual's financial situation to financial literacy, and the endogeneity of financial literacy to exposure to credit counseling. Our results show credit counseling substitutes for financial literacy. Individuals with better financial literacy are 60% less likely to use credit counseling. These results suggest credit counseling provides a safety net for poor financial literacy.
Keywords: D10; D12; I22; 330; Credit Counseling; Financial Advice; Financial Literacy; Household Finance